Global Sustainable Development Report 2016 - United Nations Department of Economic; Social Affairs (United Nations, 2016)
This report brings together a range of existing scientific assessments and reviews global progress and future sustainable development pathways in an integrated way. It responds to the 2012 Rio+20 Conference mandate to contribute to strengthening the science-policy interface for sustainable development. Major international conferences and summits in 2015 – on financing for development, sustainable development, and climate change – have defined a new sustainable development agenda for the next 15 years. At all levels, from global to local, attention is turning to implementing this ambitious agenda. This is the context in which this year’s Global Sustainable Development Report appears. Given the adoption of the 2030 Agenda for Sustainable Development with its sustainable development goals (SDGs), the report adopts the SDGs as its scope. True to its mandate, the report is designed as an assessment of assessments. It endeavors to present a range of scientific perspectives and to be policy-relevant but not policy-prescriptive. Like its predecessors, it continues to explore possible approaches and vantage points from which to examine the science-policy interface, as well as scientific approaches that can inform policies building upon integration and interlinkages across sustainable development goals, sectors, and issues.